Asymmetric electron redistribution in niobic-oxygen vacancy associates to tune noncovalent interaction in CO2 photoreduction - Di, Jun (2024)
The role of vacancy associates in photocatalytic CO2 reduction is an open question. Herein, the Nb─O vacancy associates (VNb─O ) are engineered into niobic acid (NA) atomic layers to tailor the CO2 photoreduction performance. The intrinsic charge compensation from O to Nb around Nb─O vacancy associates can manipulate the active electronic states, leading to the asymmetric electron redistribution. These local symmetry breaking sites show a charge density gradient, forming a localized polarization field to polarize nonpolar CO2 molecules and tune the noncovalent interaction of reaction intermediates. This unique configuration contributes to the 9.3 times increased activity for photocatalytic CO2 reduction. Meantime, this VNb─O NA also shows excellent photocatalytic activity for NO3 - -NH4 + synthesis, with NH4 + formation rate up to 3442 µmol g-1 h-1 . This work supplies fresh insights into the vacancy associate design for electron redistribution and noncovalent interaction tuning in photocatalysis.